OTONOMI DESA ADAT PAKRAMAN BERDASARKAN PERDA PROVINSI BALI NOMOR 4 TAHUN 2019 TENTANG DESA ADAT DI BALI - Fauziyah Fauziyah (Universitas Islam Darul Ulum, 2021)
The State of Indonesia recognizes and respects the existence of indigenous villages as mandated by the constitution in article 18B paragraph (2) of the Constitution of the Republic of Indonesia of 1945. Furthermore, Law No. 6 of 2014 concerning Villages was born as an application to the mandate of consensus. Pakraman Indigenous Village is one of the legal alliances in Indonesia where it has the right of autonomy to regulate its own household. For the sake of legal certainty, a Regional Regulation is needed as a legal basis to regulate the form or scope of autonomy of pakraman customary villages. The latest Regional Regulation on Indigenous Villages in Bali which was then issued in 2019 is quite a bit reviewed. This research aims to analyze how the form of autonomy in Bali based on Bali Provincial Regulation No. 4 of 2019 concerning Balinese Customary Villages, along with their boundaries in relation to the power of the Unitary State of the Republic of Indonesia. The method used is normative legal research. The approach used is the conceptual approach and the legislative approach.